2021
DOI: 10.24059/olj.v25i1.2475
|View full text |Cite
|
Sign up to set email alerts
|

A Pandemic of Busywork: Increased Online Coursework Following the Transition to Remote Instruction is Associated with Reduced Academic Achievement

Abstract: Under normal circumstances, when students invest more effort in their schoolwork, they generally show evidence of improved academic achievement.  But when universities abruptly transitioned to remote instruction in Spring 2020, instructors assigned rapidly-prepared online learning activities, disrupting the normal relationship between effort and outcomes.  In this study, we examine this relationship using data observed from a large-scale survey of undergraduate students, from logs of student activity in the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Considering their relative rarity in this large sample, it is possible that many instructors were unaware of these opportunities. Also, considering that many instructors were overwhelmed by the sudden transition to remote instruction (Carey, 2020), it makes sense that most instructors might default to known coursework formats with shallow learning curves, even if an increased volume of such activities might not have been beneficial for student learning (Motz, Quick, Wernert, & Miles, 2021). Next we explore these hypotheses, examining the profile of instructors who used collaborative tools during remote instruction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering their relative rarity in this large sample, it is possible that many instructors were unaware of these opportunities. Also, considering that many instructors were overwhelmed by the sudden transition to remote instruction (Carey, 2020), it makes sense that most instructors might default to known coursework formats with shallow learning curves, even if an increased volume of such activities might not have been beneficial for student learning (Motz, Quick, Wernert, & Miles, 2021). Next we explore these hypotheses, examining the profile of instructors who used collaborative tools during remote instruction.…”
Section: Resultsmentioning
confidence: 99%
“…Survey items were written specifically with the goal of understanding how the transition to remote instruction due to COVID-19 affected the faculty and student experience, in collaboration with Indiana University's Center for Survey Research. A full analysis of these results is beyond the scope of any single research article, and unrelated aspects of the survey findings have been described elsewhere (Jaggars et al, 2021;Motz, Quick, Wernert, & Miles, 2021). The full survey instruments and de-identified responses to all closed-ended survey items (including those not described in the present study) are available at .…”
Section: Methodsmentioning
confidence: 98%
“…Before pandemic, during face-to-face instructions, the instructors or PLAs could walk around the room and monitor student activities in face-to-face instruction, ultimately leading to improved academic achievements. In contrast, studies [7] report students complaining about online classes being too much work. This may be because instructors were under pressure to quickly shift their in-person teaching to online methods and send out as many online learning activities to keep students engaged.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have reported [2] that student engagement decreased after the transition to online instruction but have also found that assignments that did not require classroom attendance increased student engagement in the class. Furthermore, under pressure to rapidly put their course materials online [5], instructors modified their courses to include online busywork that did not constitute meaningful learning activities, which had a detrimental effect on student outcomes at scale. These findings are discussed in contrast with other situations in which increased engagement does not necessarily lead to improved learning outcomes, and in comparison with the broader relationship between effort and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Online conversions. Modest online facsimiles took the form of scheduling synchronous remote classes on Zoom or a similar platform, reducing the number of assignments and exams, shifting to pass/fail grading (Johnson et al, 2020), or assigning online "busywork" (Motz, Quick, Wernert, & Miles, 2021). A myriad of structures emerged.…”
Section: Instructional Breakthrough For Humormentioning
confidence: 99%